COMPONENTS OF EFFECTIVE MANAGEMENT MECHANISMS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Effective management is the backbone of any successful organization. It ensures that resources are used efficiently, goals are achieved, and the organization remains competitive in a dynamic environment. Effective management mechanisms encompass various components, each playing a critical role in the overall success of the organization.